Construction of a rodent neural network-skeletal muscle assembloid that simulate the postnatal development of spinal cord motor neuronal network - Yu, Haiyang; Yang, Shangbin; Chen, Yuanfeng; Wu, Chuangran; Xu, Jing; Yang, Yue; Wu, Rongjie; Guo, Yinan; Chen, Zhen; Ding, Ying; Zeng, Xiang; Li, Ge; et al. (Scientific reports, 2025)
Neuromuscular diseases usually manifest as abnormalities involving motor neurons, neuromuscular junctions, and skeletal muscle (SkM) in postnatal stage. Present in vitro models of neuromuscular interactions require a long time and lack neuroglia involvement. Our study aimed to construct rodent bioengineered spinal cord neural network-skeletal muscle (NN-SkM) assembloids to elucidate the interactions between spinal cord neural stem cells (SC-NSCs) and SkM cells and their biological effects on the development and maturation of postnatal spinal cord motor neural circuits. After coculture with SkM cells, SC-NSCs developed into neural networks (NNs) and exhibited a high proportion of glutamatergic and cholinergic neurons, low proportion of neuroglia and gamma-aminobutyric acidergic neurons, and increased expression of synaptic markers. In NN-SkM assembloids, the acetylcholine receptors of SkM cells were upregulated, generating neuromuscular junction-like structures with NNs. The amplitude and frequency of SkM cell contraction in NN-SkM assembloids were increased by optogenetic and glutamate stimulation and blocked by tetrodotoxin and dizocilpine, respectively, confirming the existence of multisynaptic motor NNs. The coculture process involves the secretion of neurotrophin-3 and insulin growth factor-1 by SkM cells, which activate the related ERK-MAPK and PI3K-AKT signaling pathways in NNs. Inhibition of the ERK-MAPK and PI3K-AKT pathways significantly reduces neuronal differentiation and synaptic maturation of neural cells in NN-SkM assembloids, while also decreasing acetylcholine receptor formation on SkM cells. In brief, NN-SkM assembloids simulate the composition of spinal cord motor NNs and respond to motor regulatory signals, providing an in vitro model for studying postnatal development and maturation of spinal cord motor NNs.